Functional classes of bronchial mucosa genes that are differentially expressed in asthma - Catherine Laprise; Robert Sladek; André Ponton; Marie-Claude Bernier; Thomas J. Hudson; Michel Laviolette (2004)
Asthma pathogenesis and susceptibility involves a complex interplay between genetic and environmental factors. Their interaction modulates the airway inflammation and remodelling processes that are present even in mild asthma and governs the appearance and severity of symptoms of airway hyperresponsiveness. While asthma is felt to develop as the result of interaction among many different genes and signalling pathways, only a few genes have been linked to an increased risk of developing this condition. We report the results of expression microarray studies using tissue obtained from bronchial biopsies of healthy controls and of subjects with allergic asthma, both before and following inhaled corticotherapy. We identified 79 genes that show significant differences in expression (following Bonferroni cutoff using p < 6.6 × 10-6 to correct for multiple testing) in asthmatics compared to controls at significance levels. These included 21 genes previously implicated in asthma, such as NOS2A and GPX3, as well as new potential candidates, such as ALOX15, CTSC and CX3CR1. The expression levels of one third of these transcripts were partially or completely corrected following inhaled corticosteroid therapy. The study shows that bronchial biopsies obtained from healthy and asthmatic subjects display distinct expression profiles. These differences provide a global view of physiopathologic processes active in the asthmatic lung and may provide invaluable help to clarify the natural history of asthma.